Peningkatan Kesadaran Dan Partisipasi Siswa Pada Kegiatan Literasi Dalam Pengelolaan Perpustakaan Di SMA Negeri 2 Lubuk Pakam - Monalisa Frince Sianturi; Audy Silvana Br Sinaga; Arnensi Evrinawati Simbolon; May Lisabeth Harianja (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Community Service (PkM) is a program carried out by FKIP students at HKBP Nommensen University, Medan. Community Service Activities are based on Law of the Republic of Indonesia Number 20 of 2003 concerning the National Education System in Article 20 Paragraph 2 which states that: